2016
DOI: 10.1016/j.jfda.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of three tissue-cultured Dendrobium species and their wild correspondences by headspace gas chromatography–mass spectrometry combined with chemometric methods

Abstract: Different provenances of Dendrobiums had characteristic chemicals and showed remarkable quantity discrepancy of common compositions. The similarity evaluation disclosed that the accumulation of volatile compounds in Dendrobium samples might be affected by their provenance. Principal component analysis showed that the first three components explained 85.9% of data variance, demonstrating a good discrimination between samples. Gas chromatography-mass spectrometry techniques, combined with chemometrics, might be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Although some methods, such as gas chromatography–mass spectrometry fingerprint (Chen et al 2016), fourier transform infrared spectroscopy (Chen et al 2015), capillary electrophoresis (Zha et al 2009) have been applied for the authentication of Dendrobium species, they are complicated needing professional operators, cost- and time-consuming, and hard to distinguish the commercial samples that share similar textures, chemical and microscopic characteristics after processing and preparation as decoction pieces. In recent decades, molecular techniques, such as DNA barcoding (Wilson et al 2019) and real-time PCR (Sobrino-Gregorio et al 2019) have been used to differentiate many closely related species with significant advantages in the fields of taxonomy, phylogeny, evolution and breeding (Teixeira da Silva et al 2016), especially for the morphological analogues or complexes including Dendrobium species.…”
Section: Introductionmentioning
confidence: 99%
“…Although some methods, such as gas chromatography–mass spectrometry fingerprint (Chen et al 2016), fourier transform infrared spectroscopy (Chen et al 2015), capillary electrophoresis (Zha et al 2009) have been applied for the authentication of Dendrobium species, they are complicated needing professional operators, cost- and time-consuming, and hard to distinguish the commercial samples that share similar textures, chemical and microscopic characteristics after processing and preparation as decoction pieces. In recent decades, molecular techniques, such as DNA barcoding (Wilson et al 2019) and real-time PCR (Sobrino-Gregorio et al 2019) have been used to differentiate many closely related species with significant advantages in the fields of taxonomy, phylogeny, evolution and breeding (Teixeira da Silva et al 2016), especially for the morphological analogues or complexes including Dendrobium species.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly different metabolic profiling between C. roseus and Vinca minor was characterized using GC-MS and LC-MS methods [ 20 ]. Recently, metabolomic characterization based on non-targeted GC-MS of medicinal Dendrobium plants was also reported [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al separated and relatively quantified 63 volatile compounds, with 53 being identified from three Dendrobium spp. samples by HS-GC–MS [ 62 ].…”
Section: Advanced Analytical Techniques For Quality Standard Of Tcmmentioning
confidence: 99%